Inggris - Wulandari, Andi Sri Rezky; Rahmah, Andi; Nurmiati, Nurmiati (Amsir Law Journal, 2023)
This research examines the dynamics of business licensing policy and the adoption of the Online Single Submission (OSS) system as a risk-based solution in public services. This research assesses the legal aspects of the business licensing policy, particularly focusing on OSS in order to be able to evaluate its impact on the efficiency and effectiveness of public services. Using a juridical approach, this research conducts a thorough legal analysis of relevant laws, regulations and judicial precedents that emphasise the importance of the OSS system in simplifying licensing procedures and reducing administrative burden. Through a risk-based approach, the OSS promotes transparency, accountability and fairness as well as enhances legal certainty which also minimises the risk of corruption of authorised state officials. The study also identifies many challenges such as data privacy issues, security from cybercrime and potential conflicts in the decision-making process that will be addressed to improve the effectiveness and sustainability of the OSS system. This research will contribute to the study of law and public administration providing valuable insights for policy makers and the OSS system. The OSS policy also promotes good governance, facilitates economic growth and improves the quality of public services.